Confounding factors affecting faecal egg count reduction as a measure of anthelmintic efficacy - Morgan, Eric R. (2022)
Increasing anthelmintic resistance (AR) in livestock has stimulated growing efforts to monitor anthelmintic effectiveness (AE) on livestock farms. On-farm assessment of AE relies on measuring the reduction in faecal egg count (FEC) following treatment; and if conducted rigorously, qualifies as a formal FEC reduction test (FECRT) for AR. Substantial research effort has been devoted to designing robust protocols for the FECRT and its statistical interpretation; however, a wide range of factors other than AR can affect FEC reduction on farms. These are not always possible to control, and can affect the outcome and repeatability of AE measurements and confound the on-farm classification of AR using FECRT. This review considers confounders of FEC reduction, focusing on gastrointestinal nematodes of ruminants, including host and parasite physiology and demography; pharmacokinetic variation between drugs, parasites and hosts; and technical performance. Drug formulation and delivery, host condition and diet, and seasonal variation in parasite species composition, can all affect AE and hence observed FEC reduction. Causes of variation in FEC reduction should be attenuated, but this is not always possible. Regular monitoring of AE can indicate a need to improve anthelmintic administration practices, and detect AR early in its progression. Careful interpretation of FEC reduction, however, taking into account possible confounders, is essential before attributing reduced FEC reduction to AR. Understanding of confounders of FEC reduction will complement advances in FECRT design and interpretation to provide measures of anthelmintic efficacy that are both rigorous and accessible.